2020
DOI: 10.1097/mrr.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aerobic fitness in individuals with and without nonspecific chronic low back pain: a pilot study

Abstract: Aerobic fitness assessment in patients with low back pain (LBP) may help clinicians to plan how to progress the aerobic training. This was a pilot study designed to evaluate the performance of people with LBP on two different aerobic fitness tests performed on a treadmill and to compare the measure of aerobic fitness between people with LBP and healthy individuals. Ten people with LBP and 10 healthy individuals underwent two aerobic fitness protocols, the modified Bruce and maximum incremental test protocols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Poor endurance seems a factor for increased risk of suffering from back pain as well [ 17 ]. However, in general, research on the association of PF and back pain is still inconclusive [ 15 , 16 , 17 , 18 , 19 ], which may also be attributed to the overall low volume of studies, the risk of bias, and the poor quality of the evidence [ 21 ]. Despite our results brining new data in line with the body of literature supporting a positive effect of general PF on back pain, further and deeper research should be carried out in this sense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor endurance seems a factor for increased risk of suffering from back pain as well [ 17 ]. However, in general, research on the association of PF and back pain is still inconclusive [ 15 , 16 , 17 , 18 , 19 ], which may also be attributed to the overall low volume of studies, the risk of bias, and the poor quality of the evidence [ 21 ]. Despite our results brining new data in line with the body of literature supporting a positive effect of general PF on back pain, further and deeper research should be carried out in this sense.…”
Section: Discussionmentioning
confidence: 99%
“…The role of aerobic exercise and cardiorespiratory fitness is further recognized in previous studies [ 64 , 65 ]. However, other authors have presented contrasting findings on cardiorespiratory fitness: for instance, Fernandes et al [ 18 ] compared this variable in individuals with and without clinically diagnosed back pain, finding no significant differences and adding that the aerobic performances of both groups in different activities were comparable. A systematic review adds that data on the effect of aerobic fitness on back pain is contradictory to the date [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a cross-sectional survey of 2,766 well-functioning community-dwelling older adults found a negative association between LBP and self-reported, but not objectively-measured physical function [ 6 ]. Moreover, although some authors have demonstrated an impact of LBP on endurance performance [ 7 ], a recent study did not confirm significant difference for endurance performance between individuals with and without non-specific LBP [ 8 ]. These previous studies primarily included patients with chronic LBP (>12 weeks), with the relationship between LBP and functional outcomes in patients with non-chronic LBP (<12 weeks) still underreported.…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare burden associated with LBP is high, not only due to direct costs (medical appointments, exams, medications, and hospitalizations) but also loss of work productivity [2,3]. However, despite LBP's clinical and economic significance, studies examining the relationship between the presence and intensity of LBP with reported and observed physical function and health related quality of life (HRQoL) have had inconsistent findings [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%